Potensi jamur Purpureocillium lilacinum sebagai endofit pengendali nematoda puru akar pada tanaman tomat (Solanum lycopersicum L.) - Pamungkas, Dimas Bagus; Swibawa, I Gede; Aeny, Titik Nur; Pramono, Sudi (Jurnal Proteksi Agrikultura, 2024)
This research aims to study the effectiveness of the fungus Purpureocillium lillacinum as a control agent for root-knot nematodes and its potential as an endophyte in tomato plants. The study was conducted from August 2023 until Februaty 2024 in the greenhouse of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The experiment followed a Completely Randomized Design (CRD) consisting of five treatments with five replications. The treatments tested were different dosage levels of P. lilacinum fungus culture on rice; 5g, 10g, 20g, 20g, 40g and 0g per polybag containing 2.5 kg of planting medium. P. lilacinum was applied by spreading it on the planting medium and soaking the roots in a suspension of fungal conidia before transplanting. Seven days after transplanting, the tomato plants were infested with 2000 root-knot nematode (RKN) Meloidogyne sp. eggs. Ninety days after planting, the plants were harvested to observe nematode populations in the roots and soil, root damage, and fungal colonization in the roots. Nematode (J2) in roots were extracted using a modified Baerman method from 5g of root samples, while nematode (J2) in the soil were extraced by sieving and sentrifugation with a sugar solution from 300 cc of soil. Root damage was assessed using a root gall score 0-10, and fungal colonies in the roots was expressed as a percentage after staining using tryphan blue. Data were analyzed for variance and followed by the Least Significant Difference (LSD) test for at a 5% significance level. The results showed that the application P. lilacinum at 40 g per plant was effective in reducing root-knot nematode damage, as well as decreasing RKN (J2) populations in the soil and roots. Additionally, P. lilacinum was confirmed to be endophyte in tomato plants.